LANGUAGE IS A TOOL OF COMMUNICATION IN ECONOMIC FIELDS AND ITS IMPORTANCE IN EFFECTIVE BUSINESS - Madmarova Feruzakhon (University Research Base, 2024)
In this article, the importance of language knowledge in the economy is discussed and the need for it is increasing at a high level, and the fact that language as a means of communication is one of the main factors in the development of business or its opposite. Also the issues of using economic terms in foreign languages in accordance with the situation are considered.